Benign Osteoblastoma Located in the Parietal Bone - Lee, Yong Gun (The Korean Neurosurgical Society, 2010)
Benign osteoblastoma is an uncommon primary bone tumor, extremely rare in calvarium. We present a case of a 25-year-old female with an osteoblastoma of parietal bone which was totally resected. The authors discussed the clinical presentation, radiographic finding, differential diagnosis and management of the benign calvarial osteoblastoma with a review of the literature.